Coping and psychological distress in elite adolescent soccer players following professional academy deselection - Blakelock, D. J.; Chen, M. A.; Prescott, T. (Journal of Sport Behavior, 2018)
Comparable to elite athletes from other sport disciplines, elite soccer players have been found to experience heterogeneous reactions and outcomes following being released/ deselected from professional clubs. For example, while some players have reported increased psychological well-being (e.g., increased relaxation and enjoyment of life; Brown & Potrac, 2009), other players have been found to experience reduced transition quality. Examples of reduced transition quality found in media reports and empirical research include players needing a longer period of time to adjust to a post-soccer life, reduced well-being (e.g., having no purpose) and experiencing various forms of psychological distress such as anxiety, depression, humiliation, reduced self-worth, identity confusion, social dysfunction, and suicide (Blakelock, 2018; Blakelock, Chen & Prescott, 2016; Brown & Potrac, 2009; Conn, 2017).